2008
DOI: 10.4319/lom.2008.6.336
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial deployments of an autonomous in situ instrument for long‐term monitoring of copper (II) in the marine environment

Abstract: We developed an autonomous, in situ instrument to detect dissolved copper in seawater, suitable for deployment on time scales from weeks to a month. A commercially available in situ nitrate analyzer (YSI 9600) was adapted to measure copper (II) by chemiluminescence. Modifications included construction of a photomultiplier (PMT)-based detector and flow-cell, the use of more chemically resistant plastics for parts in contact with the reagents, addition of an online acidification step, and optimization of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…Linearity was observed to 200 nM in pure water and 100 nM in seawater (data not shown). Sensitivity, represented by the slope of the calibration curve, was always greater in pure water then in seawater by a factor of 3–5, consistent with previous studies (Holm et al, 2008). It is therefore important to match the standard matrix to that of the samples.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Linearity was observed to 200 nM in pure water and 100 nM in seawater (data not shown). Sensitivity, represented by the slope of the calibration curve, was always greater in pure water then in seawater by a factor of 3–5, consistent with previous studies (Holm et al, 2008). It is therefore important to match the standard matrix to that of the samples.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies (Zamzow et al, 1998; Holm et al, 2008) have optimized reaction pH, and concentrations of 1,10-phenanthroline, TEPA, CDAB, and hydrogen peroxide for maximum signal intensity. We wanted to see whether the concentration of reagents injected into the cells had an impact on signal intensity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ chemical analyzers based on flow techniques have been developed for Fe and Mn (e.g., Massoth, 1991;Chin et al, 1992;Okamura et al, 2001;Sarradin et al, 2005;Vuillemin et al, 2009) and Cu (Holm et al, 2008), but the reported limits of detection of these submersible analyzers (Table 3), which were originally designed for monitoring metal dynamics in the vicinity of hydrothermal vent systems or in coastal regions, are inadequate for open-ocean determinations.…”
Section: Fiamentioning
confidence: 99%